2011
DOI: 10.1103/physreve.84.031404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic self-assembly and directed flow of rotating colloids in microchannels

Abstract: Nonequilibrium structure formation and dynamics in suspensions of superparamagnetic colloids driven by an external rotating magnetic field are studied by particle-based mesoscale hydrodynamics simulations in confined geometry. We address the fundamental question how the rotation of the colloids about their own axes can be converted into a translational motion by breaking the symmetry of the confining geometry. We study a two-dimensional system of colloids with short-range repulsive interactions, which mimics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…The effects of confinement on such a system are also quite interesting not only from a fundamental viewpoint, but also from a viewpoint of applications to microfluidics 42,43 . Such effects on rotors in a fluid have recently been numerically studied by Götze and Gompper 22,23 . It is quite interesting to study how such spatial confinements affect all the dynamical phases we reported and the transition between them.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of confinement on such a system are also quite interesting not only from a fundamental viewpoint, but also from a viewpoint of applications to microfluidics 42,43 . Such effects on rotors in a fluid have recently been numerically studied by Götze and Gompper 22,23 . It is quite interesting to study how such spatial confinements affect all the dynamical phases we reported and the transition between them.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In experiment the couples can be applied only by acting with an electric field on a permanent electric dipole moment, or with a magnetic field on a permanent magnetic dipole moment. Since the fields generated by polarization or magnetization are spatially non-uniform, they also exert a force on a dipole.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical simulations have exhibited the effect of spinning particles on fluid flow. 15,16 It would be of interest to pursue such simulations in a comparison with the above theoretical calculation of the conveyor belt effect in a tube.…”
Section: Discussionmentioning
confidence: 97%